The impact of electronic cigarettes on the lung health of young adults: An integrative review (Research, Society and Development, 2024)
Introduction: Originally created as an alternative to conventional cigarettes and banned in 2009, electronic cigarettes have gained popularity among young people. Although marketed as safer, they are potentially more harmful, containing addictive substances like nicotine and THC, which affect neurological development. Studies highlight pulmonary risks, emphasizing the need for awareness campaigns. Methodology: This article aims to present an integrative literature review on the impact of electronic cigarettes on the pulmonary health of young adults. Twenty articles were analyzed, selected from the PubMed, SciELO, and BVS databases, using specific descriptors and rigorous inclusion criteria to address the guiding question. Results: The results, analyzed descriptively, highlight the impact of electronic cigarettes on users' pulmonary health. Key findings include EVALI (e-cigarette or vaping product use-associated lung injury), respiratory failure, inflammation, and lung infections, along with long-term effects such as cognitive and psychological impairment. Discussion: Battery-powered electronic cigarettes, designed to deliver nicotine or other e-liquids, were initially promoted as a smoking cessation tool. However, their use has surged among adolescents and young adults due to aggressive marketing. EVALI, a lung injury associated with these devices, presents severe symptoms and primarily affects young men. Conclusion: The growing use of electronic cigarettes is causing severe lung injuries, liver problems, leukocyte abnormalities, and psychological issues, particularly among young people. The ban in Brazil is insufficient in the face of the expanding market. Studies underscore the need for further research on EVALI, with clear diagnostic protocols, to understand and mitigate long-term impacts.